Znaczenie intymności i zaangażowania interpersonalnego w regulacji dystansu w związkach miłosnych we wczesnej dorosłości - Mamot, Anita Weronika; Smykowski, Błażej (Człowiek i Społeczeństwo, 2021)
The aim of the theoretical and empirical studies presented in the article was to analyze the relationship between intimacy and interpersonal commitment experienced in love relationships during early adulthood. The study involved 172 participants asked completed Interpersonal Commitment Questionnaire and Intimacy Questionnaire. The results of the research confirmed the occurrence of a relationship between interpersonal commitment and experienced intimacy, but not in all their dimensions. It was also established that the length of the relationship does not matter for the dimensions of both experienced intimacy and interpersonal commitment. For some of them, the type of love relationship is significant.